Sekolah menengah atas berprestasi tinggi dan rendah di Kota Makassar, Indonesia - Bakkareng, Hasmirati (2018)
The examination results of the Education Department of South Sulawesi Province for secondary school in Makassar shows the differenere between schools in Makassar. Results show that the majority of schools are at an urisatisfactory level. However, there are some schools that achieve a high level of performance. This situation prompted researcher to conduct a multi-site case study to identify the leadership styles of principals, teachers' attitudes and behaviors, school facilities, parent and community involvement, and school culture of high-performing and low-performing schools in Makassar. 1n order to achieve this objective, a qualitative approach using multi-case study research design was utilized. Semi structured interviews, observations, and document analysis were used to collect data. The sample consists of two highperforming and two low-performing secondary schools in the city of Makassar. Four school principals and 12 teachers of the schools were chosen using purposive sampling technique to be respondents of the study. Data was analyzed using thematic analysis technique. This study found that the factors that differentiate between high-performing and low-performing schools were; (1) The leadership styles of principals that emphasizes on teaching and learning, controlling students' discipline, ensuring teachers' understand the school's vision, and conducting teachers development programs, (2) The level of commitment, motivation and self-efficacy of teachers were at high level, (3) The school culture which focuses on students learning, and orderly school environment. This study has contributed to the development of knowledge in the field of high-performing schools in Indonesia. This study suggests that if a school wants to achieve high-performing level, principals must exercise leadership styles emphasizing on teaching and learning, ensure that teachers' commitment, motivation and self-efficacy are at high level, and has a culture that focuses on teaching and learning, and orderly school environment.